Nutritional related blood composition of goats supplemented with different level of soy waste - Hassan, Makhzumi Noor (2018)
The availability of agricultural by-products seems promising to be used as animal feed. Soy waste is one of the agricultural by-products which is extensively included in diets of goat. Due to the availability and cheap price of soy waste, along with its nutritional value, it may decrease the total cost of feed, as well as supporting and contributing to the goat’s health. However, there are limited studies on the effect of soy waste supplementation on enhancing the health performance of goats. Thus, this study was conducted to compare the effect of supplementation of soy waste and its effect on nutritional related blood profile in breeder goats. Eighteen female Boer cross adult goats were chosen and arranged into three different groups (n = 6) and assigned according to their feed formulation (Control; no supplementation of soy waste, SW 10; supplemented with 10% soy waste and SW 20; supplemented with 20% soy waste). Blood sample was taken before and after three weeks of soy waste supplementation. The samples were then analysed for selected parameters (calcium, total protein, glucose, cholesterol and fatty acid composition). Proximate analysis of soy waste supplemented feed was done and revealed significant different between crude protein, crude fiber and dry matter as compared to the control group.Glucose, total protein, calcium and cholesterol level in serum from SW 10 and SW 20 showed that it is higher than the control group. Fatty acid analysis of feed and serum showed unsaturated fatty acid was significantly higher than saturated fatty acid for soy waste supplemented groups as compared to the control. Overall, group SW 20 shows the highest value of all blood parameters analysed in this study. Thus, this study indicates that different level of soy waste supplementation affects certain nutritional related blood profile in goat.